INTERNALISASI NILAI MULTIKULTURALISME DAN KERUKUNAN ANTARUMAT BERAGAMA DALAM MASYARAKAT - Syukri Fathudin; Vita Fitria (Jurnal Penelitian Humaniora, 2012)
This research discussed on how the tolerance between societies can be created through the pattern and process of the internalization of multiculturalism value to society in Potorono, Banguntapan, Bantul. The values appeared through such a long processes of society dynamic where they lived. In descriptive qualitative method, the portrait of that society can be revealed to analyze deeper the practices or processes of the internalization of multiculturalism value that can unite the society with their differences. This research aimed at revealing casuistically the process of the internalization of multiculturalism value and its correlation with tolerance between societies, as well as the factors which influence the societies to maintain their multiculturalism value. The objective of this research is to know the processes of internalization of multiculturalism value and to understand its correlation with tolerance in society, thus it can be an interactive room for each people in society to find the solution and alternative answer for any possible conflict that may be happened. This research applied qualitative research which aimed at gaining deeper understanding on the phenomenon recorded on the field of the research. To understand deeply and holistically, the analysis of meanings, values and deeper   understanding   on   the   character   of   society   of   Potorono, Banguntapan, Bantul is needed.  The approach applied in this research is exploratory   descriptive   and   explanatory   study   case.   It   is   through exploratory the data found in the research, then explaining the data found and final process is improving the explanations comparatively to certain similar phenomenon and proving that this kind of explanation can be applied to another situation. The research findings are: 1) the awareness of society of Potorono to maintain the values of tolerance has been there for long time ago and has been practiced hereditarily 2) the social interaction with a new community happened with adaptive process and step by step through religious and social activities, 3) the majority of native people have kinship relation, thus it caused the process of internalization of value easier, 4) the values appeared are tolerance, togetherness, care and respectfulness.